Los lugares de la memoria y de la acción política en Guatemala. Justicia transicional, políticas del reconocimiento y ficciones de secularismo - Carlos Arturo Salamanca Villamizar (Revista de Estudios Sociales, 2015)
I analyze here the importance of religion in Guatemala during the conflict and post-conflict periods through: i) the “new” structures of social mobilization during the sixties and seventies; ii) religion as rhetorical practice and field of power; iii) the territorialization of memory policies; and iv) the processes of recovering historical memory. I argue against theories about secularism that coincide with some interpretations of identity that tend to separate and reproduce binary oppositional categories that prevent recognition of ambiguous, dynamic and complex social identities. I explain why a historical-anthropological perspective on space facilitates a more effective understanding of mobile and transversal societies in their processes of becoming constituted, political positioning, and interpreting the past.